Economic evaluation of livestock enterprises supported by the expert hands project in rural areas - Satar, Muharrem; Arikan, Mehmet Saltuk; Peker, Arzu (Selcuk Universitesi, Veteriner Fakultesi, 2023)
Aim: With this work; it is aimed to reveal the cost and income factors of cattle and small ruminant enterprises supported by the expert hands project and to make an economic analysis of the annual profit-loss status of the enterprises. Materials and Methods: The main material of the study consists of the primary data obtained from 50 entrepreneurs who benefited from the expert hands project in 2021 and from 36 enterprises in total, 18 of which are cattle and 18 of small ruminant enterprises that accepted to participate in online survey applications. Results: From the findings; feed costs account for 39.46% of the main factors that make up the cost in enterprises, followed by labor (33.48%), electricity-water (6.45%), live fixture depreciation (6.25%) and veterinarian-health (5,08%) costs were determined. It has been determined that cattle enterprises make an average of 200,56 $ profit, and small ruminant enterprises make an average of 1946,06 $ profit.. Conclusion: Within the scope of this project implemented, it is possible to say that the fact that livestock activities are carried out by trained and expert entrepreneurs, especially in rural areas, has a positive effect on the average profitability of enterprises. © 2023 Selcuk Universitesi, Veteriner Fakultesi. All rights reserved.
Kırsal alanda uzman eller projesi ile desteklenen hayvancılık işletmelerinin ekonomik açıdan değerlendirilmesi
Keywords: Cattle; economic analysis; expert hands project; small ruminant